Microvesicles released from multiple myeloma cells are equipped with ectoenzymes belonging to canonical and non-canonical adenosinergic pathways and produce adenosine from ATP and NAD+. (3rd August 2018) - Morandi, F.; Marimpietri, D.; Horenstein, A. L.; Bolzoni, M.; Toscani, D.; Costa, F.; Castella, B.; Faini, A. C.; Massaia, M.; Pistoia, V.; Giuliani, N.; Malavasi, F.
ABSTRACT: Multiple myeloma (MM) derives from malignant transformation of plasma cells (PC), which accumulate in the bone marrow (BM), where microenvironment supports tumor growth and inhibits anti-tumor immune responses. Adenosine (ADO), an immunosuppressive molecule, is produced within MM patients' BM by adenosinergic ectoenzymes, starting from ATP (CD39/CD73) or NAD + [CD38/CD203a(PC-1)/CD73]. These ectoenzymes form a discontinuous network expressed by different BM cells. We investigated the expression and function of ectoenzymes on microvesicles (MVs) isolated from BM plasma samples of patients with MM, using asymptomatic forms of monoclonal gammopathy of undetermined significance (MGUS) and smoldering MM (SMM) as controls. The percentage of MVs expressing ectoenzymes at high levels was higher when derived from MM patients than controls. BM CD138 + PC from MM patients expressed high levels of all ectoenzymes. Paired MVs samples confirmed a higher percentage of MVs with high ectoenzymes expression in MM patients than controls. Pooled MVs from MM patients or controls were tested for ADO production. The catabolism of ATP, NAD +, ADPR and AMP to ADO was higher in MVs from MM patients than in those from controls. In conclusion, our results confirmed the hypothesis that MVs in MM niche are main contributor of ADO production. The ability of MVs to reach biological fluids strongly support the view that MVs may assume diagnostic and pathogenetic roles.